Analisis Determinan Kinerja Perusahaan Keagenan Kapal: Studi Empiris di Pelabuhan Tanjung Emas - Syarifah Adelia Febriyanti; Sulistyowati Sulistyowati; Andar Sri Sumantri (Port Management and Maritime Administration Journal, 2025)
This study examines the factors affecting Ship Agency Company Performance (Y) at Tanjung Emas Port, Semarang. The focus is on four independent variables: Waiting Time Perception (X1), Loading and Unloading Productivity (X2), Document Handling (X3), and Human Resources (X4). Using a quantitative approach and multiple linear regression analysis, data were collected from 100 employees across 27 agency companies. The results indicate that all four independent variables have a positive and significant partial effect on company performance. Waiting Time Perception (X1) was identified as the most dominant factor, with a coefficient of β=0.322β = 0.322β=0.322 and tcount=3.152t_{count} = 3.152tcount​=3.152, suggesting that docking time efficiency (influenced by pilot services and vessel intensity) is the key determinant of agency performance. The coefficient of determination (Adjusted R2R^2R2) is 0.370, indicating that 37% of the variation in performance is explained by the model, while the remaining 63% is influenced by external factors such as weather and macro policies. This study underscores the importance of managing port time effectively and improving Human Resources competencies to enhance agency performance in congested and digitized maritime environments, offering strategic recommendations for regulators and port managers.